Huwaran/hulmahan atbp. the film writings of Johven Velasco - Velasco, Johven 1948-2007; David, Joel. (Quezon City University of the Philippines Press, 2009)
A compilation of film articles by Johven Velasco and his contribution as a film director, educator and writer in the film industry in the Philippines.
Keywords: Velasco, Johven -- 1948-2007 -- Criticism and interpretation; Motion picture actors and actresses -- Philippines; Film criticism -- Philippines; Motion pictures -- Philippines -- Evaluation